Comparison of the Influence of Instagram Reels and TikTok on Increasing Adolescents' Attitudes to the Dangers of Using Fashion Braces - Ninda Anisa Erika Safura; Syamsulhuda Budi Musthofa; Zahroh Shaluhiyah (International Journal Labs, 2025)
This study aims to analyze the influence of health promotion through social media, specifically Instagram Reels and TikTok, on improving adolescent attitudes toward the dangers of fashion dental braces usage. This quasi-experimental research used a non-equivalent pre-test post-test control group design with 120 junior high school students aged 12-16 years in Karangroto Village, Genuk District, Semarang City. Respondents were divided into three groups: Instagram Reels intervention group (40 respondents), TikTok intervention group (40 respondents), and control group (40 respondents). Data were collected using validated questionnaires and analyzed using Wilcoxon signed-rank test, Mann-Whitney test, and Kruskal-Wallis test. Results showed significant improvement in positive attitudes from 42.5% to 90% in the Instagram Reels group and from 45% to 95% in the TikTok group. Statistical analysis revealed significant differences in attitude scores before and after intervention (p=0.000) for both intervention groups. However, no significant difference was found between Instagram Reels and TikTok effectiveness (p=0.377). Both intervention groups showed significantly better outcomes compared to the control group (p=0.000). This study concludes that both Instagram Reels and TikTok are effective media for health promotion regarding fashion dental braces dangers among adolescents, with TikTok showing slightly better improvement in attitude scores.